Nonsteroidal anti-inflammatory drug use is associated with improved activities of daily living and rehabilitation in older adult patients following a fracture: a retrospective cohort study - Eiji Kose; Hidetatsu Endo; Hiroko Hori; Shingo Hosono; Chiaki Kawamura; Yuta Kodama; Takashi Yamazaki; Toshimi Kimura (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background Insufficient rehabilitation due to postfracture pain can result in muscle atrophy and joint contractures, which may affect the improvement of activities of daily living (ADL). This study investigated the impact of using nonsteroidal anti-inflammatory drugs (NSAIDs) on the improvement of ADL in older adult patients with fractures admitted to a convalescent rehabilitation unit. Methods Of 489 older adult patients with fractures from January 2017 to June 2019, 261 fulfilled the requirements for this retrospective cohort analysis. Patients who had convalescent rehabilitation following a fracture were categorized into two groups: those who used NSAIDs and those who did not. The functional independence measure-total gain (FIM-total) score, which was used for evaluating ADL, was the main outcome measure. We ascertained the independent relationship between NSAIDs use and rehabilitation outcomes using a multiple linear regression analysis. Covariates selected to correct bias included age, sex (male), BMI, hypertension, dementia, cardiovascular disease, cerebrovascular disease, upper limb paralysis, femoral fracture, lumbar compression fracture, thoracic compression fracture, pelvic fracture, patellar fracture, FIM-total at admission, number of drugs, acetaminophen use. Results The mean participant age was 82.3 ± 7.4 years, 69 (26.4%) of them were men, and 94 (36%) used NSAIDs. Multiple linear regression analysis revealed that NSAIDs use was independently associated with FIM-total gain during hospitalization (β=2.311, P=0.013). Conclusions These findings suggest that the appropriate use of NSAIDs may play a beneficial role in maximizing rehabilitation outcomes. However, careful monitoring for potential adverse effects is essential, particularly in older adults.